Regional effects on employer-provided training: Evidence fromapprenticeship training in Switzerland - Samuel Muehlemann; Stefan C. Wolter (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
This paper uses regional variation in labor markets, the industry structure and the education system to explain the training decisions of firms. Using a representative firmlevel data set, the results show that firms are less likely to provide training if the number of competing firms situated in the same geographical area is high. Furthermore, the supply of potential apprentices affects the training decision positively through an improved matching process. In addition, the expected ability of apprentices also has a positive impact, whereas a more developed system of full-time schooling options for young people who have completed their compulsory schooling reduces the likelihood of a firm providing training.
Keywords: 330; Betrieb; Ausbildungsverhalten; betriebliche Berufsausbildung; regionale Disparität; regionale Faktoren; regionaler Arbeitsmarkt; Wirtschaftsstruktur; Wettbewerb; Berufsbildungssystem; duales System; schulische Berufsausbildung; Personalpolitik; Bildungsökonomie; Schweiz